Dark tourism and pilgrimage - Daniel H. Olsen; Maximiliano Korstanje; C.A.B. International (Oxfordshire, United Kingdom : Cabi, 2020)
The first book to cover the intersections between dark tourism and pilgrimage, this multi-disciplinary resource reviews theories and case studies of dark tourism and pilgrimage sites, as well as how experience design comes into play. It also suggests avenues of future research to guide further exploration into this under-appreciated area of travel
Keywords: Collective memory; Psychosocial aspects; Heritage tourism; Dark tourism